Fractals, architecture and sustainability - Parashar, Rinku; Bandyopadhyay, Abir (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The concept of fractals has brought about exhilarating and innovative changes deepening and broadening our understanding about the nature, culture and science. Sustainability as understood is an attempt looking at three dimensions- social ,economic and environmental. Architecture accomplishes some of the basic human needs namely aesthetics, functionality and sustainability. Fractal architecture with its unique feature of organic assemblage of units is better endowed to answer questions of sustainability than many other form of architecture. The fractal theme serves as a framework or reference for organizing an intellectual and aesthetic presentation in order to explain the reality that ‘everything in the universe (nature) is connected to everything else.’ The concept of fractal explains nature, where sustainability is a current concern. The topic of Fractal is a realization of the natural world expressed mathematically where the structure of every piece holds the key to the whole structure. The application of fractal theory in architecture is a new concept. The following research paper will discuss about fractals, their existence in architecture and how further they can be related to sustainability <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>